2006
DOI: 10.1177/0265407506068264
|View full text |Cite
|
Sign up to set email alerts
|

Female waist-to-hip and male waist-to-shoulder ratios as determinants of romantic partner desirability

Abstract: This study examines the effects of body shape (women's waist-to-hip ratio and men's waist-to-shoulder ratio) on desirability of a potential romantic partner. In judging desirability, we expected male participants to place more emphasis on female body shape, whereas females would focus more on personality characteristics. Further, we expected that relationship type would moderate the extent to which physical characteristics were valued over personality. Specifically, physical characteristics were expected to be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
37
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 34 publications
(70 reference statements)
6
37
0
5
Order By: Relevance
“…In contrast, other research in which body shape was manipulated found that muscularity, a variable closely related to WCR, was associated with perceived dominance (Frederick & Haselton, 2007). Although they did not directly explore dominance as a potential mediator of the relationship between WCR and attractiveness, Frederick and Haselton (2007) did find a similar pattern to Braun and Bryan's (2006) research. Specifically, women rated men described as "brawny," "built," or "toned" (i.e., low WCR) as both more dominant and sexual desirable, but less likely to be committed to a partner, than men described as "slender," "typical,"…”
Section: Dominancementioning
confidence: 80%
See 4 more Smart Citations
“…In contrast, other research in which body shape was manipulated found that muscularity, a variable closely related to WCR, was associated with perceived dominance (Frederick & Haselton, 2007). Although they did not directly explore dominance as a potential mediator of the relationship between WCR and attractiveness, Frederick and Haselton (2007) did find a similar pattern to Braun and Bryan's (2006) research. Specifically, women rated men described as "brawny," "built," or "toned" (i.e., low WCR) as both more dominant and sexual desirable, but less likely to be committed to a partner, than men described as "slender," "typical,"…”
Section: Dominancementioning
confidence: 80%
“…Braun and Bryan (2006) found that the perceived dominance of men was related to the desire for a short-term, sexual relationship, but not a long-term relationship. However, they found that men's body shape had little to do with the perception of dominance.…”
Section: Dominancementioning
confidence: 97%
See 3 more Smart Citations